How to prove the following equation? \begin{eqnarray} \sin 3A+\cos 3A&=&\left(\cos A-\sin A\right)\left(1+2\sin 2A\right)\\ \end{eqnarray}

Let's start with the left hand side. \begin{eqnarray} LHS&=&sin 3A+\cos 3A\\ &=&\sin \left(2A+A\right)+\cos \left(2A+A\right)\\ &=&\sin 2A\cos A+\cos 2A\sin A+\cos 2A\cos A-\sin 2A\sin A\\ &=&\left(2\sin A\cos A\right)\cos A+\left(\cos ^2A-\sin ^2A\right)\sin A+\left(\cos ^2A-\sin ^2A\right)\cos A-\left(2\sin A\cos A\right)\sin A\\ &=&\cos ^3A-\sin ^3A-\sin ^2A\cos A+\sin A\cos ^2A-2\sin ^2A\cos A+2\sin A\cos ^2A\\ \end{eqnarray}

Than, I have no idea what I should do.

Just try to expand the RHS.

\begin{eqnarray} RHS&=&\left(\cos A-\sin A\right)\left(1+2\sin 2A\right)\\ &=&\cos A-\sin A+2\sin 2A\cos A-2\sin 2A\sin A\\ &=&\cos A-\sin A+4\sin A\cos ^2A-4\sin ^2A\cos A\\ &=&?\\ \end{eqnarray}

Maybe there are something wrong.

Anyone can tell me what I should do?

Thank you for your attention.


Following your method we have

$$\sin3A+\cos3A=\sin2A(\cos A-\sin A)+\cos2A(\cos A+\sin A)$$

Now,$$\cos2A(\cos A+\sin A)=(\cos^2A-\sin^2A)(\cos A+\sin A)=(\cos A-\sin A)(\cos A+\sin A)^2=(\cos A-\sin A)(1+\sin2A)$$ as $\sin2A=2\sin A\cos A$

Can you take it from here?

  • $\begingroup$ @CasperLi, how about this? $\endgroup$ – lab bhattacharjee Oct 1 '13 at 18:42
  • $\begingroup$ Nice, I can prove cos2A(cosA+sinA)=(cosA−sinA)(1+sin2A) $\endgroup$ – Casper Oct 2 '13 at 12:59
  • $\begingroup$ so, sin2A(cosA−sinA)+(1+sin2A)(cosA−sinA)=(cosA−sinA)(sin2A+1+sin2A), and (1+sin2A+sin2A)=(1+2sin2A),rigth? ---->Proved $\endgroup$ – Casper Oct 2 '13 at 13:11
  • $\begingroup$ @CasperLi, yes, right you are $\endgroup$ – lab bhattacharjee Oct 2 '13 at 15:22

Using$$\sin3A=3\sin A-4\sin^3A,\cos3A=4\cos^3A-3\cos A$$

$$\sin3A+\cos3A=3\sin A-4\sin^3A+4\cos^3A-3\cos A=3(\sin A-\cos A)-4(\sin^3A-\cos^3A)$$

Now, $\displaystyle\sin^3A-\cos^3A=(\sin A-\cos A)(\sin^2A+\sin A\cos A+\cos^2A)=(\sin A-\cos A)\left(1+\frac{\sin2A}2\right)$


sin 3A +cos 3A= sin(2A+A)+cos(2A+A)

= sin 2A.cos A+cos 2A.sin A+cos2A.cos A-sin A.sin 2A

= 2.sin A.cos A.cos A+(1-2sin^2 A).sin A+(2cos^2 A-1).cos A-sin A.2sin A.cos A

= 2.sin A.cos^2 A+sin A-2sin^3 A+2cos^3 A-cos A-2sin^2 A.cos A

= 2sin A(1-sin^2 A)+sin A-2sin^3 A+2cos^3 A-cos A-2(1-cos^2 A).cos A

= 3sin A-4sin^3 A+4cos^3 A-3cos A

= 3(sin A-cos A)-4(sin^3 A-cos^3 A)

Remember: sin^3 A-cos^3 A= (sin A-cos A)((sin A-cos A)^2+3.sin A.cos A)

= 3(sin A-cos A)-4(sin A-cos A)((sin A-cos A)^2+3.sin A.cos A)

= (sin A-cos A)(3-4((sin A-cos A)^2+3.sin A.cos A))

= (sin A-cos A)(3-4(1-2sin A.cos A+3 sin A.cos A))

= (sin A-cos A)(3-4(1+sin A.cos A))

= (sin A-cos A)(-1-4.sin A.cos A)

= (cos A-sin A)(1+4.sin A.cos A)--> remember sin 2A= 2.sin A.cos A

= (cos A-sin A)(1+2.sin 2A)-->proved

  • 1
    $\begingroup$ we can directly use the formula of $\sin3A,\cos3A$ instead of deriving them, right? $\endgroup$ – lab bhattacharjee Oct 1 '13 at 18:22
  • $\begingroup$ Right, I just explain to him how to derive it, so she can understand step by step. $\endgroup$ – akusaja Oct 1 '13 at 18:23

LHS sin(2A+A)+cos(2A+A) = sin2A.cosA + cos2A.sinA + cos2A.cosA- sin2A.sinA = 2sin A.cos^2A +(cos^2A-sin^2A).sinA + (cos^2A-sin^2A).cosA -2sin^2A.cosA
=cos^3A-sin^3A + sinA.cosA(2cosA+cosA- sinA-2sinA)
=(cosA-sinA)(cos^2A+cosA.sinA+sin^2A) +sinA.cosA(3cosA-3sinA) =(cosA-sinA)(1+cosA.sinA)+3sinAcosA(cosA-sinA) =(cosA-sinA)(1+4cosA.sinA) =(cosA-sinA)(1+2sin2A) =RHS

  • $\begingroup$ Please, use MathJax (i.e. LaTeX commands) for mathematical notations. $\endgroup$ – Taroccoesbrocco Jun 7 '18 at 12:12

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.